APPRAISAL SYSTEM: TEACHER’S AND STUDENTS’ AFFECT, JUDGMENT AND APPRECIATION IN KNOWLEDGE CONSTRUCTION - Acep Haryudin; Wawan Gunawan; Bachrudin Musthafa (English Review: Journal of English Education, 2025)
This study aims to investigate how the Appraisal system specifically the Attitude category, which includes Affect, Judgment, and Appreciation is realized in verbal interactions between teachers and students, and how it contributes to knowledge construction within the context of a bilingual primary school classroom. A qualitative approach with a case study design was employed, with data collected through participant observation, audio-visual recordings, and classroom interaction transcripts. The analysis was based on the Appraisal framework, mapping evaluative expressions with a focus on Attitude. The findings reveal that both teachers and students employed all three subcategories of Attitude, though with differing emphases. The teacher demonstrated a balanced use of Affect (41.86%), Judgment (20.93%), and Appreciation (37.21%), while the students predominantly used Affect (50%), followed by Appreciation (35.71%) and Judgment (14.29%). Affect emerged as a means of expressing emotional engagement, Judgment reflected the shaping of scientific behavior and learning ethics, and Appreciation fostered understanding of scientific objects and processes. Evaluative language not only builds conceptual meaning but also shapes a supportive and reflective classroom climate, strengthening students’ scientific identity. This study highlights the significant role of evaluative language in shaping the cognitive, social, and emotional dimensions of learning. The findings offer practical implications for teachers in designing meaningful and value-rich classroom interactions that support the process of knowledge construction.